Alterations in the fat body cells of rhinocricus padbergi (Diplopoda) resulting from exposure to substrate containing sewage sludge - De Souza, Raphael Bastão [UNESP]; Fontanetti, Carmem Silvia [UNESP] (Oxford University Press (OUP), 2012)
Abstract The final disposal of residues generated at sewage treatment plants (STPs) has become a major problem for cities, due to the increase in the amount of treated sewage. One of the alternatives for the residue, labeled sewage sludge, is its reuse in agriculture and in degraded soil. However, not all pathogens and metals present in it are eliminated during treatment. Diplopods have been used as bioindicators in ecotoxicological tests as they are constantly in close contact with the soil. Owing to this fact, the purpose of this study was to expose specimens of the diplopod Rhinocricus padbergi to substrate containing sewage sludge collected at STPs to analyze morphological alterations in their parietal and perivisceral fat body, where substances are stored. The exposures were held for 7, 15, or 90 days at different concentrations of sewage sludge (control, 1%, 10%, and 50%). The parietal fat body showed no alterations in any of the three exposure periods or concentrations. Alterations in the perivisceral fat body were observed for all exposure periods. According to the results, we suggest that the sludge used has toxic agents responsible for changing the animal's perivisceral fat body. © 2012 Microscopy Society of America.
Keywords: acute exposure; histochemistry; histology; millepede; soil toxicity; STP; subchronic exposure; animal; arthropod; cytochemistry; cytology; drug effect; fat body; microscopy; pollutant; sewage; Animals; Arthropods; Environmental Pollutants; Fat Body; Histocytochemistry; Microscopy; Sewage; Animalia; Diplopoda; Rhinocricus padbergi